Simulation Study of Poly-Caprolactone, Chitosan, and Vinyl Ester Resin-coated Stainless Steel to Improve Corrosion Behavior, Bioactivity, and Biodegradability - (:unkn) unknown (AMG Transcend Association, 2022)
Heterogeneous materials are usually found in industrial and chemical centers, such as metallic alloy, polymer blending, porous and cracked materials, and especially composites. We exhibited expanded detailed studies on the integration of bonding between poly-caprolactone (PCL), chitosan and vinyl ester resin (VER), and stainless steel (SS) with h-BN substrates. Using h-BN dielectrics leads us towards a suitable improvement in mobility relative and increasing surface activities. Furthermore, we exhibited that the integration of h-BN with stainless steel (SS) exhibits unique advantages compared to exfoliated graphene. We offered higher resistance and anti-corrosion for stainless steel by forming these polymer layers on the surface sheet. Therefore, biopolymer strongly can be suggested as a perfect antifouling coating solution owing to its broad-spectrum antibacterial, antifungal, and anti-algal properties, along with amazing film-forming properties. Although atomic coordinates are adjusted by this work to reduce the molecular energy, conformational changes in the polymers might be considered to obtain the macromolecules pair correlation function. Gyration rays and end-to-end distance distributions of the chains have been applied to measure polymers' flexibilities quantitatively.